2023
DOI: 10.1002/ana.26745
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Glutamatergic and Serotonergic Connectivity in Visual Snow Syndrome and Migraine with Aura

Francesca Puledda,
Ottavia Dipasquale,
Benjamin J. M. Gooddy
et al.

Abstract: ObjectiveNeuropharmacological changes in visual snow syndrome (VSS) are poorly understood. We aimed to use receptor target maps combined with resting functional magnetic resonance imaging (fMRI) data to identify which neurotransmitters might modulate brain circuits involved in VSS.MethodsWe used Receptor‐Enriched Analysis of Functional Connectivity by Targets (REACT) to estimate and compare the molecular‐enriched functional networks related to 5 neurotransmitter systems of patients with VSS (n = 24), healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…A study by Puledda et al [ 20 ▪▪ ] indicated that both glutamatergic and serotoninergic neurotransmission might be involved in the pathophysiology of VSS using Receptor-Enriched Analysis of Functional Connectivity by Targets (REACT) combined with resting functional MRI data. Changes in glutamatergic-enriched connectivity in the dorsal anterior cingulate cortex/middle cingulate cortex (ACC/MCC) might be linked to deregulation of normal attentional functions and sensory processing integration in VSS.…”
Section: Neuroscientific Research Techniquesmentioning
confidence: 99%
“…A study by Puledda et al [ 20 ▪▪ ] indicated that both glutamatergic and serotoninergic neurotransmission might be involved in the pathophysiology of VSS using Receptor-Enriched Analysis of Functional Connectivity by Targets (REACT) combined with resting functional MRI data. Changes in glutamatergic-enriched connectivity in the dorsal anterior cingulate cortex/middle cingulate cortex (ACC/MCC) might be linked to deregulation of normal attentional functions and sensory processing integration in VSS.…”
Section: Neuroscientific Research Techniquesmentioning
confidence: 99%
“…Additionally, techniques like biofeedback [ 64 ] and meditation [ 65 ] may also enhance endogenous alpha rhythms. Second, at the level of neurotransmitters, there is growing evidence that serotonergic pathways, especially thalamocortical projections might lead to an imbalance in inhibitory or excitatory modulation of the visual cortex [ 66 – 68 ]. Here, pharmacological studies to examine effects on VSS and visual symptoms in migraine using the EEG as potential markers might be an interesting way forward [ 66 ].…”
Section: Clinical or Therapeutic Implicationsmentioning
confidence: 99%
“…The recent publica9on of a neurotransmi@er atlas by Hansen et al offers a promising avenue for such personalized interven9ons (Hansen et al, 2022). By compiling norma9ve maps of receptor and transporter densi9es, this atlas is a pivotal reference for discerning the neurochemical profile of various brain disorders (Funck et al, 2022;Hansen et al, 2022;Puledda et al, 2023). Yet, its implementa9on in focal brain diseases involving the white ma@er, like stroke, remains challenging.…”
Section: Introduconmentioning
confidence: 99%